The English Proficiency Paradox: Why Non-native Generation Z have Speaking and Writing Difficulties Despite Digital Fluency - Abigail Nadine; Annisa Ananda; Ester Monica; Samuel Sihombing (PT. Intelek Cendikiawan Nusantara, 2024)
Generation Z in Indonesia includes individuals born between 1997 and 2012, with a population of approximately 75 million, or 27% of the total population. Generation Z spend most of their time playing social media, they are closely related to the media as technology develops in their generation. They are known as ‘digital natives’, they are highly connected to technology and digital interaction and are highly sensitive to social and environmental issues. Undeniably, social media is very much a part of Gen Z’s lives. About 80% of them use social media, and 70% of them use social media as a way to get information and the latest news. Through social media, Gen Z in Indonesia is also familiar with the English language. They sometimes interact in English and receive content in English. But what is very unfortunate is that many of them still use English passively. This means that they only understand when reading and listening, but struggle when speaking and writing. In Indonesia, social media started to develop in the early 2000s with the first platform called Friendster. Since then, the use of social media has continued to grow with the launch of Facebook and Twitter in the mid-2000s. The use of social media will grow to 170 million users by 2021. At that time, applications such as Instagram and TikTok began to appear, which are now widely used by Generation Z. As the years go by, the development of social media, especially in Indonesia, is increasing. The use of English in social media interaction is increasing as many teenagers use social media. This is because platforms such as Instagram encourage users to use abbreviations and acronyms in English. In addition, more and more foreign content can be consumed by Indonesians. Social media also tends to have an informal language style, often using slang and popular phrases. Overall, the increased use of English on social media reflects globalization trends and the need to communicate effectively in the digital age. Despite the heavy use of English, Gen Zers still often struggle to communicate directly in English. When it comes to everyday conversation, few young people in Indonesia can use English. In EF Education First’s 2022 English Proficiency Index report, Indonesia ranks 81st out of 111 countries surveyed. In Indonesia, the most tested subjects are reading and writing, as well as tense and grammar. But in the world of work, what is needed is the ability to argue, how to communicate with foreigners, and how to use their skills to build new products or ideas. So it’s the speaking and listening skills that are really needed and important to communicate. There are also many young people who understand English, but are not brave enough to speak it. That’s because they’re afraid of being judged, especially in terms of grammar